School Costs, Short-Run Participation, and Long-Run Outcomes : Evidence from Kenya - Evans, David K.; Ngatia, Mũthoni (World Bank, Washington, DC, 2018)
Access to school has risen dramatically in recent decades, with large gains from reducing costs. Few studies report long-term impacts, however. This paper reports the impact of an educational intervention that reduced out-of-pocket schooling costs for children in poor communities in Kenya by providing school uniforms. The program used a lottery to determine who would receive a school uniform. Receiving a uniform reduced school absenteeism by 37 percent for the average student (7 percentage points) and by 55 percent for children who initially had no uniform (15 percentage points). Eight years after the program began, there is no evidence of sustained impact of the program on highest grade completed or primary school completion rates. A bounding exercise suggests no substantive positive, long-term impacts. These results contribute to a small literature that demonstrates the risk of fade-out of initial impacts of education investments.